Marine island biogeography. Response to comment on 'Island biogeography: patterns of marine shallow‐water organisms'. (5th October 2016) - Hachich, Nayara F.; Bonsall, Michael B.; Arraut, Eduardo M.; Barneche, Diego R.; Lewinsohn, Thomas M.; Floeter, Sergio R.
Abstract: In this response we have incorporated data on gastropod and seaweed biodiversity referred to by Ávila et al . (2016, Journal of Biogeography, doi:10.1111/jbi.12816 ) to allow an updated analysis on marine shallow‐water biogeography patterns. When compared to the biogeography patterns reported in Hachich et al . (2015, Journal of Biogeography, 42, 1871–1882), we find (1) no differences in the patterns originally reported for reef fish or seaweeds, (2) minor differences in gastropod species–area and species–age patterns and (3) a significant difference for the gastropod species‐isolation pattern. In our original work, we reported that there was limited evidence that gastropod species richness was influenced by island isolation; however, our new analysis reveals a power‐model relationship between these variables. Thus, we are now able to conclude that gastropod species diversity, whose dispersal capacity is intermediate between seaweeds (lowest) and reef fish (highest), is also influenced by island isolation.